2019
DOI: 10.1186/s12913-019-4467-5
|View full text |Cite
|
Sign up to set email alerts
|

Is there a volume-quality relationship within the independent treatment centre sector? A longitudinal analysis

Abstract: BackgroundThe number of independent treatment centres (ITCs) has grown substantially. However, little is known as to whether the volume-quality relationship exists within this sector and whether other possible organisational factors mediate this relationship. The aim of this study is to gain a better understanding of such possible relationships.MethodsData originate from the Dutch Health and Youth Care Inspectorate (IGJ) and the Dutch Patients Association. We used longitudinal data from 4 years (2014–2017) inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 54 publications
0
6
1
Order By: Relevance
“… 50 , 52 - 54 One contribution from the United States and the Netherlands shows that the volume-quality relationship also persist within the ITC sector, however, this relationship appears to be weaker. 51 , 55 Different from the previous studies, our results do not indicate that a volume-quality relationship exists for the 5 treatments included in this study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“… 50 , 52 - 54 One contribution from the United States and the Netherlands shows that the volume-quality relationship also persist within the ITC sector, however, this relationship appears to be weaker. 51 , 55 Different from the previous studies, our results do not indicate that a volume-quality relationship exists for the 5 treatments included in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…The volume-quality relationship has been demonstrated in previous research on high-risk surgical procedures in hospitals, [44][45][46][47][48][49] but is less studied for low-risk surgical outpatient procedures. 50,51 Previous research has demonstrated that high-volume hospitals provided better quality of care for low-risk invasive treatments. 50,[52][53][54] One contribution from the United States and the Netherlands shows that the volume-quality relationship also persist within the ITC sector, however, this relationship appears to be weaker.…”
Section: Discussionmentioning
confidence: 99%
“…Both these factors could have contributed to a negative patient experience and influenced their perception of overall quality of care. Some studies reported a positive relationship between patient volume and quality of basic maternal care, and postoperative infections 52 53. The alternative direction of this relationship, in which quality drives patient volume, is based on the assumption that the provision of high-quality care will attract more patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported a positive relationship between patient volume and quality of basic maternal care, and postoperative infections. 51 52 The alternative direction of this relationship, in which quality drives patient volume, is based on the assumption that the provision of high-quality care will attract more patients. This may be true in areas where patients have access to competitive health care facilities, and health care providers are incentivized for providing higher quality care.…”
Section: Discussionmentioning
confidence: 99%